Land transportation management policy in tarakan public economy - Nawir, Ing Daud; Faizal, Rahmat; Mansyur, Achmad Zultan; Riinawati, Riinawati; Jayadi, Usman (Frontiers in Built Environment, 2022)
In achieving the development of Tarakan City, the role of land transportation has an important and strategic position, so the policies need to be integrated into a single land transportation management policy and its impact on the economy of the people in Tarakan City. Various policies have been issued, to minimize the problem of land transportation, but no matter how good the policy will not work optimally as long as land transportation management is not improved. This study uses a descriptive-qualitative method because it seeks to find empirical facts with the right interpretation of the actions of existing phenomena. The results of the study: 1. The selection of land transportation in accordance with the characteristics of the City of Tarakan, and taking into account the needs and interests of all different levels of society, is able to support the effectiveness and efficiency of providing city public transportation services. 2. The development of an adequate land transportation network in Tarakan City has been able to increase the growth of the community's economic sector, increase the value/price of land, the development of the small, medium, and large scale businesses, the occurrence of product specialization between regions, the concentration and urbanization of the population, especially in areas that have opened access roads and transportation. So that there is an increase in the income of the City of Tarakan accompanied by an even distribution of goods between residents, business fields spread over several areas. In addition, there has been an increase in the number and types of finished goods and services that consumers, government, and industry can produce.